Cost-benefit aware routing protocol for wireless sensor networks with Hybrid Energy Storage System - Pais, Nuno Miguel Esteves (2011)
At the eve of a new decade, when energy concerns are at the top of the research priorities, this work presents a new cost-benefit function for wireless sensor networks (WSNs) powered by harvesting energy sources. The models rely on a Hybrid Energy Storage System (HESS) that combines a super-capacitor (SC) with a Rechargeable Battery (RB). While the SC has low energy storage capability but is capable of providing high level of energy throughput and frequent charge cycles, the RB has higher energy storage capability but limited charge cycles. Our proposal for the protocol associated with HESS assigns different weights to the residual energy in both energy storage systems whilst favouring routes with more SC energy and harvesting rates. The main innovation is the application of a new routing cost metric to prolong the network lifetime. An energy model framework has been developed in MATLAB with different application scenarios to test the proposed cost metric. The simulation results show that, by using the HESS flexible energy-aware cost-benefit function, significant extension of the network lifetime is achieved by means a balance between the energy consumption and the reliable delivery of data packets.